Chronic Urticaria and Its Impact on the Quality of Life of Nepalese Patients - Sushil Paudel; Niraj Parajuli; Rabindra Prasad Sharma; Sudip Dahal; Sudarshan Paudel (Hindawi Limited, 2020)
Chronic urticaria (CU) is a skin condition characterized by sudden and recurrent episodes of wheals, angioedema, or both and commonly associated with itching for a duration of more than six weeks. The available data indicate that urticaria markedly affects both objective functioning and subjective well-being of patients. A review of patients' records with chronic urticaria attending Civil Service Hospital from January 2018 to December 2019 was done. A detailed demographic data of all patients with chronic urticaria was also retrieved. Dermatology Life Quality Index questionnaire (DLQI) Nepalese version was used for the assessment of the impact of disease on life quality. Mann-Whitney U-test was applied to compare means, and principle component analysis for factor analysis was used. A total of 149 patients were included, with a male-to-female ratio of 1 : 1.9. The mean age of the study population was 32.86 ± 12.837 years. The mean DLQI score was 8.30 ± 6.73 with men having a significantly greater score than women (p<0.02). DLQI scores negatively correlated with age (p<0.01). There was a high internal consistency among items (Cronbach's alpha 0.89), and all items had satisfactory correlation with each other as well. Principle component extraction revealed that there were two underlying factors in the DLQI questionnaire on measuring quality of life in chronic urticaria. Males had a greater impairment in quality of life than females due to chronic urticaria. Most severe impairment was seen in symptoms/feelings subdomain. It also revealed that there were two different underlying factors in DLQI questionnaire.